Limit-Fed, High-Energy Diets Can Achieve Improved Feed Conversion Rates Without Compromising Rate of Gain When Compared to Conventional High Roughage Diets - M. A. Scilacci; M. A. Johnson; C. E. Hissong; S. P. Montgomery; A. J. Tarpoff; E. C. Titgemeyer; L. Allen; T. G. O'Quinn; G. T. Tonsor; C. I. Vahl; D. U. Thomson; W. R. Hollenbeck; et al. (Kansas Agricultural Experiment Station Research Reports, 2021)
Objective:Compare and determine the effects on animal performance between a conventional high roughage diet and a limit-fed, high energy diet during the receiving and growing phase. Study Description:Crossbred heifer calves (n = 418) originating from Texas and New Mexico were used to determine performance when limit-fed a high energy diet initially offered at 85% of feed intakes from cattle fed a conventional high roughage diet ad libitum at the Kansas State University Beef Stocker Unit. The Bottom Line:Limit-feeding a high energy diet consisting primarily of dry-rolled corn and Sweet Bran (Cargill Animal Nutrition, Blair, NE) can improve rate of gain while significantly decreasing dry matter consumption over conventional high roughage diets fed ad libitum, and cattle exhibit greater muscling and fat deposition.
Keywords: limit feeding; growing calves; feed conversion